2012
DOI: 10.1007/s00586-012-2480-z
|View full text |Cite
|
Sign up to set email alerts
|

A study investigating the validity of modified Tokuhashi score to decide surgical intervention in patients with metastatic spinal cancer

Abstract: Purpose Predicted survival of a patient is the most important parameter that helps to guide the treatment of a patient with metastatic spinal cancer. We aimed to investigate the reliability of modified Tokuhashi score in the decisionmaking process in patients with metastatic spinal cancer. Methods We performed a review of our prospectively collected Metastatic Cancer Database over a period of 4 years (2007)(2008)(2009)(2010). Ninety consecutive patients who were treated for metastatic spinal cancer were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 12 publications
1
23
1
Order By: Relevance
“…However, it has not been shown to be accurate in determining survival. 11 This study obtained results that agree with the described lack of precision in determining the survival of patients affected by metastatic spinal disease. For the patients in Group A, the survival concordance rate was better (63.4%) than that observed in patients in Group B (30%).…”
Section: Discussionsupporting
confidence: 81%
“…However, it has not been shown to be accurate in determining survival. 11 This study obtained results that agree with the described lack of precision in determining the survival of patients affected by metastatic spinal disease. For the patients in Group A, the survival concordance rate was better (63.4%) than that observed in patients in Group B (30%).…”
Section: Discussionsupporting
confidence: 81%
“…The paper by Gakhar et al [43], which showed that in a retrospective review of some 90 patients, the survival rate was much better in patients who were expected to have a short survival rate as indicated by the score. Indeed 66.6 % of their patients had a different actual survival rate from that predicted by the Tokuhashi score.…”
Section: Tumoursmentioning
confidence: 99%
“…The scoring system was tested again by Tokuhashi in 2009 showing a precision of 88.0 % (Tokuhashi et al 2005(Tokuhashi et al , 2009. Other studies validating the Tokuhashi Revised score on patients with spinal metastases found an overall precision between 71 and 88 % (Yamashita et al 2011;Tokuhashi et al 2009;Ulmar et al 2007b), but recent studies have reported moderateto-low overall precision between 33 and 64 % (Wang et al Lee et al 2013;Gakhar et al 2012;Pointillart et al 2011a, b). In a study from 2012 by Quraishi et al (2013), the Tokuhashi Revised score was validated in a cohort of patients with MSCC with a moderate overall precision on 66 %.…”
Section: Discussionmentioning
confidence: 97%
“…Because oncological treatment methods are constantly evolving, resulting in improved survival within the individual types of cancer (Pointillart et al 2011;Gakhar et al 2012;Lee et al 2013), and because of the diverse conclusions from studies validating the Tokuhashi Revised and the Tomita scoring systems on patients with spinal metastases, we found it is of relevance to assess the validity of these scoring systems in a large, recent, consecutive, and prospective cohort of patients with MSCC unselected for surgical and non-surgical treatment.…”
Section: Introductionmentioning
confidence: 98%